Ethnobotany of the Zingiberaceae Family as Traditional Medicine for the Bugis Community in the Subdistrict of Dalam Bugis in Pontianak City, West Kalimantan - Sepsamli, Letus; Syamswisna (Program Studi Biologi, Fakultas Teknik, Universitas Samudra, 2025)
The community of Kelurahan Dalam Bugis, Pontianak City, preserves its ancestral heritage by using Zingiberaceae plants as a source of medicine. Various types of Zingiberaceae plants are used as traditional medicinal ingredients. The purpose of this study is to examine local wisdom and the diversity of Zingiberaceae plants that are useful as conventional medicine by the people of Kelurahan Dalam Bugis, Pontianak City. The method applied is purposive sampling. Information on the use of Zingiberaceae as medicinal ingredients was obtained from 35 informants. Data were collected through semi-structured interviews, observations, and documentation. There are 9 types of plants from the Zingiberaceae family that are useful as medicinal ingredients in treating diseases. As many as 13 types of diseases are treated using plants from the Zingiberaceae family. The people of Kelurahan Dalam Bugis Pontianak still maintain the use of Zingiberaceae plants in traditional medicine because they are inexpensive and effective in treating diseases.